Neurobehavioral And Oxidative Stress Alterations Following Methylmercury And Retinyl Palmitate Co-Administration In Pregnant And Lactating Rats And Their Offspring (2018)
Fish consumption and ubiquitous methylmercury (MeHg) exposure represent a public health problem globally. Micronutrients presented in fish affects MeHg uptake/distribution. Vitamin A (VitA), another fish micronutrient is used in nutritional supplementation, especially during pregnancy. However, there is no information about the health effects arising from their combined exposure. The present study aimed to examine the effects of both MeHg and retinyl palmitate administered to pregnant and lactating rats. Thirty Wistar female rats were orally supplemented with MeHg (0,5 mg/Kg/day) and retinyl palmitate (7500 μg RAE1/Kg/day), either individually or in combination from the gestational day 0 to weaning. In dams, maternal behavior was scored. In neonatal and infant offspring, associative learning and neurodevelopment were evaluated. Further periadolescent male and female pups were assessed for open field, habituation and object recognition using episodic-like memory paradigm. Maternal and offspring redox parameters were evaluated. Our results showed no effects of MeHg-VitA co-administration in the quality of maternal care but showed subtle alterations in the pro-oxidant response of the hippocampus. In offspring, MeHg-VitA co-exposure affected early associative learning in neonatal pups, with no further modifications in neurodevelopment, and no locomotor or exploratory alterations in later developmental stages. Habituation was altered in a sex-dependent manner, but no overall memory disturbances were encountered.